2022
DOI: 10.3389/fpsyg.2022.795039
|View full text |Cite
|
Sign up to set email alerts
|

Research Landscape of Artificial Intelligence and e-Learning: A Bibliometric Research

Abstract: While an increasing number of organizations have introduced artificial intelligence as an important facilitating tool for learning online, the application of artificial intelligence in e-learning has become a hot topic for research in recent years. Over the past few decades, the importance of online learning has also been a concern in many fields, such as technological education, STEAM, AR/VR apps, online learning, amongst others. To effectively explore research trends in this area, the current state of online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…All articles in this study were obtained from the citation databases of the Science Citation Index (SCI) and Social Science Citation Index (SSCI) and were obtained from the Web of Science (WOS) created by the Institute of Science Information (ISI). Thus, high-quality literature datasets were provided, which can be used in bibliometric research and scientific research ( Vílchez-Román et al, 2020 ; Su et al, 2021 ; Tang et al, 2021 ; Jia et al, 2022 ). Despite the growing importance of neuroscience in the field of marketing, to date, less research has been conducted on the application of bibliometric methods in the field.…”
Section: Dataset and Research Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…All articles in this study were obtained from the citation databases of the Science Citation Index (SCI) and Social Science Citation Index (SSCI) and were obtained from the Web of Science (WOS) created by the Institute of Science Information (ISI). Thus, high-quality literature datasets were provided, which can be used in bibliometric research and scientific research ( Vílchez-Román et al, 2020 ; Su et al, 2021 ; Tang et al, 2021 ; Jia et al, 2022 ). Despite the growing importance of neuroscience in the field of marketing, to date, less research has been conducted on the application of bibliometric methods in the field.…”
Section: Dataset and Research Methodologymentioning
confidence: 99%
“…However, data cleaning cannot be judged by other analysis tools or keywords and must be filtered manually. Therefore, in this study, based on the practices of Wang and Ngai (2020) and Jia et al (2022) , the collected samples were filtered manually. In filtering, two assistant university professors and two researchers of this study jointly read the abstract of the paper and confirmed whether the research topic and content were consistent with this research topic in multiple ways.…”
Section: Dataset and Research Methodologymentioning
confidence: 99%
“…Consequently, four articles were excluded. Based on the literature screening criteria proposed by Su et al (2020) and Jia et al (2022), three team members independently examined the papers to screen out the articles that were inconsistent with the research topic. These controversial papers would be voted by our team to decide whether to be eliminated.…”
Section: Review Materialsmentioning
confidence: 99%
“…Journals of SSCI and SCI included in the Web of Science (WOS) were the main literature data resources. The WOS offers high-quality literature and is frequently used in bibliometric research ( Su et al, 2020 ; Jia et al, 2022 ). The search term rules in this study are as follows: TS = [(“fMRI” or functional magnetic resonance imaging) or (eye-tracking) or (event-related) or (electroencephalography or “EEG”) or (eye fixation related potential or “efrp”) or (neurois) or (Neuroscience) or (neuro information systems) or (neuro information systems)].…”
Section: Data Collectionmentioning
confidence: 99%
“…To reduce errors in the keyword search, irrelevant papers were excluded. The deletion rule is based on Wang and Ngai (2020) and Jia et al (2022) . The method in which Taskin and Al (2019) conducted a standardized process of data cleaning, including the standardization process of author names, was used as a reference in this study.…”
Section: Data Collectionmentioning
confidence: 99%